2001
DOI: 10.1309/yn14-k8u4-5flj-dgje
|View full text |Cite
|
Sign up to set email alerts
|

Is Fine-Needle Aspiration Biopsy a Practical Alternative to Open Biopsy for the Primary Diagnosis of Sarcoma?

Abstract: We reviewed the clinicopathologic features of 145 consecutive fine-needle aspiration biopsy (FNAB) specimens from 140 patients without a previous diagnosis of sarcoma. Among 138 adequate specimens, 42 bone sarcomas and 80 soft tissue sarcomas were recognized as sarcomas; histologic subtyping was easier in bone than in soft tissue sarcomas and in pediatric than in adult cases. There was no correlation in accuracy of subtyping in low- vs high-grade sarcomas. FNAB was most accurate for subtyping of skeletal osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
126
1
16

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 19 publications
6
126
1
16
Order By: Relevance
“…Foram estudados 140 pacientes com tumores ósseos (87% de correlação da biópsia) e tecidos moles (83% de correlação da biópsia), obtendo até 5% de falso-positivo ou falso-negativo em tumores ósseos e até 15% de discordância em tumores de partes moles (10)(11) .…”
Section: Discussionunclassified
“…Foram estudados 140 pacientes com tumores ósseos (87% de correlação da biópsia) e tecidos moles (83% de correlação da biópsia), obtendo até 5% de falso-positivo ou falso-negativo em tumores ósseos e até 15% de discordância em tumores de partes moles (10)(11) .…”
Section: Discussionunclassified
“…1 Others have documented similar difficulties. 13,14 For the above reasons, deeply seated soft tissue lesions that appear predominantly fatty by current imaging modalities are probably best evaluated by tissue biopsy.…”
Section: Discussionmentioning
confidence: 92%
“…7 However, the literature clearly demonstrates that one or more FNAB passes may obtain adequate material for immunocytochemistry (cell block), conventional cytogenetic analysis, flow cytometry and image analysis, and even research purposes, with informed consent of the patient. 1,3,4,8,9 Other groups of investigators have successfully used polymerase chain reaction (PCR) amplification techniques on archival FNAB cytologic smears, confirming the EWS/FLI-1 fusion product of Ewing's sarcoma, the SYT/SSX fusion product of synovial sarcoma, and the detection of Herpesvirus-8 in cases of Kaposi's sarcoma. [10][11][12] For the detection of the SYT/SSX fusion transcript by reverse transcriptase PCR, Inagaki et al 11 reported a higher sensitivity among cytologic samples (91%) compared to more traditional frozen biopsy materials (75%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations